Coverage of Gingival Fenestration Using Modified Pouch and Tunnel Technique: A Novel Approach - Sunil Pendor; Vidya Baliga; A. Muthukumaraswamy; Prasad V. Dhadse; Kiran Kumar Ganji; Kaustubh Thakare (Hindawi Limited, 2013)
Gingival fenestration defects are a rare phenomenon. Gingival fenestration means the exposure of the tooth due to loss of the overlying bone and gingiva. Though treatment of mucosal fenestration occurring in association with chronic periapical inflammation has been reported previously, the occurrence and treatment of gingival fenestration have not been documented in great detail. This report describes the occurrence of a gingival fenestration that developed secondarily to a gutka chewing habit. Treatment of the fenestration along with coverage of an adjacent recession defect in a single-step procedure using a pouch and tunnel technique is described.